An equitable and scalable approach to track fidelity of implementation in partnership with teachers - Spacciapoli, Megan; Viana, Mara; Saunders Wilder, Oliver; Sullivan, Jillian; McCallum, Tia; Wilder-Smith, Barbara (Frontiers in Education, 2022)
Social and emotional learning (SEL) is a key focus of early childhood education. A significant body of research demonstrates the critical impact of fidelity of SEL implementation on child outcomes; however, few widely-used curricula regularly assess classroom-level implementation fidelity outside of the context of research, or correlate fidelity with key areas of children’s development of these skills. Fidelity measurement often focuses on easy-to-quantify variables such as classroom environment or lesson plan adherence, and is typically treated as a single snapshot used as a moderator or co-variate when assessing child outcomes, rather than being intentionally leveraged as a systematic, ongoing process to drive implementation support or growth. In this manuscript, we present a novel, scalable approach to systematically create a series of implementation fidelity snapshots embedded within professional development. We propose a set of best practices for using ongoing, short, teacher-recorded videos to assess fidelity based on two years of developing and piloting our approach. A key component is the re-conceptualization of fidelity measurement as part of an ongoing professional development feedback ecosystem. Through a series of videos submitted across a school year, teachers receive targeted feedback and see their individual growth in practices designed to improve children’s SEL and academic outcomes. To enable the collection of a series of longitudinal fidelity data samples, we developed a platform where teachers record and upload videos of teaching practices and children engaging with their peers in specific classroom activities via a mobile application to a web-based dashboard. Each video submission request has an associated set of five ‘Look Fors’ which are shared with teachers in advance, and are designed to engage teachers in partnership in reflecting on children’s development and the application of Tools’ approach in their classrooms. Videos are viewed and coded on these sets of ‘Look-Fors’ by the teachers, and by Tools coaches who provide specific and targeted feedback in an interactive exchange. Results from an initial pilot of this approach in several hundred classrooms demonstrate feasibility and utility, and suggest that teacher-recorded videos can offer a cost-effective and scalable means to collect fidelity data on teacher practices.